Minding the gut: extending embodied cognition and perception to the gut complex - Boem, Federico; Greslehner, Gregor P.; Konsman, Jan Pieter; Chiu, Lynn (Frontiers in Neuroscience, 2024)
Scientific and philosophical accounts of cognition and perception have traditionally focused on the brain and external sense organs. The extended view of embodied cognition suggests including other parts of the body in these processes. However, one organ has often been overlooked: the gut. Frequently conceptualized as merely a tube for digesting food, there is much more to the gut than meets the eye. Having its own enteric nervous system, sometimes referred to as the “second brain,” the gut is also an immune organ and has a large surface area interacting with gut microbiota. The gut has been shown to play an important role in many physiological processes, and may arguably do so as well in perception and cognition. We argue that proposals of embodied perception and cognition should take into account the role of the “gut complex,” which considers the enteric nervous, endocrine, immune, and microbiota systems as well as gut tissue and mucosal structures. The gut complex is an interface between bodily tissues and the “internalized external environment” of the gut lumen, involved in many aspects of organismic activity beyond food intake. We thus extend current embodiment theories and suggest a more inclusive account of how to “mind the gut” in studying cognitive processes.